Risk of peripheral facial palsy following parenteral inactivated influenza vaccination in the elderly Chinese population - Yang, Tianchi; Ma, Rui; Ye, Lixia; Mei, Qiuhong; Wang, Jianmei; Feng, Yueyi; Zhou, Shaoying; Pan, Xingqiang; Hu, Danbiao; Zhang, Dandan (Frontiers in Public Health, 2023)
Background: Concern about the risk of peripheral facial palsy (PFP) following vaccination is one reason for hesitancy in influenza vaccination. However, the association between the flu vaccine and PFP is still controversial, and further evidence is urgently needed. Methods: This self-controlled case series study evaluated PFP risk following inactivated influenza vaccine in the elderly using a large linked database in Ningbo, China. Relative incidence ratios (RIRs) and 95% confidence intervals (CIs) estimated using conditional Poisson regression were utilized to determine whether the risk of PFP was increased after vaccination. Results: This study included 467 episodes, which occurred in 244 females and 220 males. 124 episodes happened within 1-91 days after vaccination, accounting for 26.7%. The adjusted RIRs within 1-30 days, 31-60 days, 61-91 days, and 1-91 days after influenza vaccination were 0.95 (95% CI 0.69 to 1.30), 1.08 (95% CI 0.78 to 1.49), 1.01 (95% CI 0.70 to 1.45), and 1.00 (95% CI 0.81 to 1.24), respectively. Similar results were found in subgroup analyses and sensitivity analyses. Conclusions: Influenza vaccination does not increase PFP risk in the elderly population. This finding provides evidence to overcome concerns about facial paralysis after influenza vaccination.